Case Report on Systemic Lupus Erythematosus - Hina Y. Rodge1 , Bibin Kurian2 , Manoj Patil3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Systemic Lupus Erythematous (SLE) is a multi-system chronic but often episodic,autoimmune condition defined by widespread inflammation of connective tissues and immune complexmediated vasculitis as well as the involvement of Antinuclear Antibodies.Case Presentation: The 11 years old female patient who was apparently alright 2 months back admittedin “Acharya Vinoba Bhave Rural Hospital Sawangi (M), Wardha,” Maharashtra on date 22/02/2020 withthe chief complaint of high-grade fever on and off since 2 months and facial puffiness since 6 days, ascites,constipation and pain in joints. The patient started experiencing fever 02 months back which was highgrade and she took treatment on an OPD basis but there was no relief. After that she was admitted at GMCChandrapur for the complaint of cough, cold, fever and oral ulcer and symptomatic treatment was given andgot discharged after 12 days. Fever, facial puffiness, pain in knee joints. The patient had undergone variousinvestigations like complete blood count, urine analysis, lipid profile, anti-nuclear antibodies (ANA), ANTIDSDNA (Anti-Double Stranded DNA). The patient was treated with antibiotics, corticosteroid, antacid,DMARD (Disease-Modifying Anti-Rheumatic Drug), a loop diuretic, antiemetic and oral paste to treatmouth ulcers. Monitor all vital signs, checked and recorded intake and output, administered medication asprescribed.Conclusion: The patient was admitted to AVBRH with chief complaints of fever on and off, facial puffiness,ascites, constipation and pain in joints. Immediate treatment was started by health team members and nowthe patient’s condition is satisfactory.